Syphilis among female sex workers in Indonesia: need and opportunity for intervention. Issue 5 (3rd June 2010) - Majid, Nurholis; Bollen, Liesbeth; Morineau, Guy; Daily, Syaiful Fahmi; Mustikawati, Dyah E; Agus, Nurhayati; Anartati, Atiek Sulistyarni; Natpratan, Chawalit; Magnani, Robert
Abstract : Objective: To study the prevalence and factors associated with syphilis among female sex workers (FSWs) in Indonesia. Methods: Direct and indirect FSWs were sampled in 10 major cities in Indonesia. A behavioural survey was conducted and samples obtained and tested for HIV (Bioline and Determine) and syphilis (RPR and Determine). Syphilis prevalence and potential factors associated with syphilis were assessed in bivariable and multivariable analysis. Syphilis prevalence among brothel-based sex workers from previous surveillance in 2003 and 2005 was compared to 2007. Results: A total of 2436 direct and 1888 indirect FSWs participated in both the behavioural and biomarker surveys. Prevalence of active syphilis (RPR≥1:8) was high among direct and indirect FSWs (7.5% vs 3.1%) and was not lower among those who had visited an STI clinic in the last 3 months. Prevalence of active syphilis was lower among those who had received at least one dose of a prior periodic presumptive treatment programme (PPT) for chlamydia and gonorrhoea with 1 g azithromycin and 400 mg cefixime compared to those who had not received PPT (3.9% vs 6.0%; p=0.008). Older age (AOR=1.4), longer duration of sex work (AOR=1.7) and PPT (AOR=0.6) were associated with active syphilis in multivariable analysis. Syphilis prevalence among brothel-based FSWs increased from 2005 to 2007 (7.8% vs 14.5%; p<0.001). Conclusions: Syphilis prevalence among FSWs in Indonesia was high and increased from 2005 to 2007. Receipt of PPT was associated with lower syphilis prevalence. Current syphilis control programmes need to be evaluated and the possibility of alternative syphilis treatment with azithromycin explored.